Evaluating Mode of Action of Acrolein Toxicity in an In Vitro Human Airway Tissue Model. (10th September 2018) - Xiong, Rui; Wu, Qiangen; Muskhelishvili, Levan; Davis, Kelly; Shemansky, Jennifer M; Bryant, Matthew; Rosenfeldt, Hans; Healy, Sheila M; Cao, Xuefei
Abstract: Acrolein is a reactive unsaturated aldehyde and is found at high concentrations in both mainstream and side-stream tobacco smoke. Exposure to acrolein via cigarette smoking has been associated with acute lung injury, chronic obstructive pulmonary diseases (COPDs), and asthma. In this study, we developed an in vitro treatment strategy that resembles the inhalation exposure to acrolein experienced by smokers and systematically examined the adverse respiratory effects induced by the noncytotoxic doses of acrolein in a human airway epithelial tissue model. A single 10-min exposure to buffered saline containing acrolein significantly induced oxidative stress and inflammatory responses, with changes in protein oxidation and GSH depletion occurring immediately after the treatment whereas responses in inflammation requiring a manifestation time of at least 24 h. Repeated exposure to acrolein for 10 consecutive days resulted in structural and functional changes that recapitulate the pathological lesions of COPD, including alterations in the beating frequency and structures of ciliated cells, inhibition of mucin expression and secretion apparatus, and development of squamous differentiation. Although some of the early responses caused by acrolein exposure were reversible after a 10-day recovery, perturbations in the functions and structures of the air-liquid-interface (ALI) cultures, such as mucin production, cilia structures, and morphological changes, failed to fully recover over the observation period. Taken together, these findings are consistent with its mode of action that oxidative stress and inflammation have fundamental roles in acrolein-induced tissue remodeling. Furthermore, these data demonstrate the usefulness of analytical methods and testing strategy for recapitulating the key events in acrolein toxicity using an in vitro model.